Uji Performansi Mesin Yanmar TS 50 Menggunakan Bahan Bakar Biodiesel dari Minyak Kepayang (Pangium Edule) - Turmizi Turmizi; Khairil Khairil; Sulaiman Thalib (Jurnal Teknik Mesin Unsyiah, 2014)
Fruit Football is a type of plant that is widely available in Aceh and is not utilized by the community. This research will be studied in experiments of fruit fooball as biofuel in diesel engines. Diesel engines are used in this test is a single cylinder four stroke engine water-cooled Yanmar brand, type TS 50 with specs: Maximum Power 5 HP, maximum rotation 2400 rpm, maximum torque 2.29 kg.m at 1600 rpm and compression ratio 17.9: 1. Performance testing is done with a diesel engine intended to determine the amount of power generated, the level of fuel consumption, specific fuel consumption and thermal efficiency. Testing is done with two variations of biodiesel fuel that B-10 and B-20 as well as diesel fuel for comparison. The results obtained from this study is that the power generated from diesel fuel is greater than the other two fuels, while more efficient fuel consumption B-20 followed by B-10 and diesel fuel. Specific fuel consumption results are varied while the higher thermal efficiencies generated by the B-20 of the B-10 and diesel fuel at high speed.